2020
DOI: 10.1111/os.12641
|View full text |Cite
|
Sign up to set email alerts
|

Debridement, Antibiotics, and Implant Retention for Acute Periprosthetic Joint Infection

Abstract: Objective: To report on our clinical outcomes and on the experience of managing acute periprosthetic joint infection (PJI) with debridement, antibiotics, and implant retention (DAIR). Methods:We performed a retrospective review of all patients who were diagnosed with acute PJI after primary hip or knee replacement surgeries and who were managed with DAIR in our prospective joint replacement registry from 2008 to 2019. The diagnosis of PJI was made according to the 2011 Musculoskeletal Infection Society (MSIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Although a 100% success rate of DAIR for Staphylococcus infection has been reported [23], most studies reported a higher failure rate of DAIR when performed to treat Staphylococcus infection [11,22,[24][25][26]. A multicenter observational study performed by Weston et al [22] reported a three-fold increased risk of failure after DAIR in cases of Staphylococcus infection.…”
Section: Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a 100% success rate of DAIR for Staphylococcus infection has been reported [23], most studies reported a higher failure rate of DAIR when performed to treat Staphylococcus infection [11,22,[24][25][26]. A multicenter observational study performed by Weston et al [22] reported a three-fold increased risk of failure after DAIR in cases of Staphylococcus infection.…”
Section: Microbiologymentioning
confidence: 99%
“…Dixon et al [ 38 ] showed that arthroscopic debridement was more effective in patients with periprosthetic infection of the knee. Though findings of a meta-analysis [ 23 ] suggested a higher infection control rate for arthroscopic debridement compared with open debridement, the results were not significantly different. The pooled infection control rate for arthroscopic DAIR was based on only a few studies.…”
Section: Introductionmentioning
confidence: 99%
“…After excluding 29 duplicates and 38 irrelevant citations based on titles and abstracts, 20 citations remained for full‐text evaluation. Following this, we further excluded 11 articles because: (i) study designs did not meet the inclusion criteria (two reviews, one case report, and one editorial) 18 , 28 , 29 , 30 ; (ii) one study was related to therapeutics 31 ; (iii) the population or sample included in three studies was not relevant 20 , 32 , 33 ; (iv) the index test in one study did not include NGS 34 ; (v) one study did not use the MSIS criteria, IDSA criteria, or ICM criteria as a reference standard; and (vi) one study involved the establishment of a PJI diagnostic model in which the data relating to NGS diagnosis could not be obtained 19 , 35 . Nine articles were finally eligible for the review 14 , 15 , 16 , 17 , 36 , 37 , 38 , 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Of these, DAIR represents the least invasive option for surgical PJI management, with previous studies reporting shorter hospital stays and lower cost in addition to functional outcomes that are comparable to primary total joint arthroplasty [ [5] , [6] , [7] ]. Unfortunately, the efficacy of DAIR for PJI treatment remains unclear, with reported failure rates of DAIR procedures in the literature varying from 0% to as much as 84% [ [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%